How Arrest Impacts Delinquency Over Time Between and Within Individuals - Mowen, Thomas J. (Youth violence and juvenile justice, 2018)
While some studies find that criminal justice contact may deter future offending, another body of research indicates that contact with the criminal justice system can increase delinquency among youth. Although research has examined the relationship between punishment and offending, from a life-course perspective, we know little about between-individual and within-individual effects of punishment across time. Using a cross-lagged dynamic panel model, results from an analysis of four waves of data from the National Longitudinal Survey of Youth 1997 demonstrate that arrest contributes to within-individual increases in delinquency across time even after baseline levels of delinquency are controlled. Between-individual results show that youth who were arrested experience significant increases in offending compared to youth never arrested even after accounting for prior offending. Finally, this study uncovers a “cumulative effect” of arrest in that each subsequent year the youth is arrested relates to increased offending irrespective of prior offending. Overall, findings suggest that arrest contributes to significant increases in delinquency even after baseline levels of offending are directly modeled.